ANALYSIS OF SOLVENCY, PROFITABILITY, FIRM SIZE, AND COMPANY AGE ON AUDIT DELAY IN ENERGY SECTOR COMPANIES LISTED ON IDX 2017-2021 - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 4 No 4 (2024): LUCRUM : Jurnal Bisnis Terapan, 2025)
This research purposed to determine the effect of analysis solvency, profitability, Firm size, and company age on audit report lag in Energy companies for the 2017 - 2021 year period. This study used secondary data. The sampling technique in this study used purposive sampling. A total of 48 companies were sampled. The analysis method for this research used descriptive analysis, and several types of evaluation were conducted using SPSS21 software. From this research, it was concluded that solvency and company age had a significant effect on audit report lag. Meanwhile, profitability and firm size did not have a significant effect on audit delay.